DEKOMPOSISI TERMAL PROPELAN KOMPOSIT BERBASIS AMONIUM PERKLORAT/HYDROXY TERMINATED POLYBUTADIENE (AP/HTPB) (THE THERMAL DECOMPOSITION ANALYSIS OF AMMONIUM PERCHLORATE/HYDROXYTERMINATED POLYBUTADIENE (AP/HTPB) COMPOSITE SOLID PROPELLANT) - Wiwiek Utami Dewi; Yulia Azatil Ismah (National Institute of Aeronautics and Space - LAPAN, 2016)
Thermal decomposition process of AP/HTPB solid propellant type RUM, 450 and 1220 were investigated by DTG60 (Differential Thermogravimetric) with operational parameters: temperature 30 – 400oC, nitrogen flow rate 50 ml/min, and heating rate 2.5 C/min. Thermal decomposition analysis will be the first step of decomposition kinetics research in determining life time of the propellant. TGA curve of propellant RUM was found to be two staged meanwhile the thermal decomposition of propellant 450 and 1220 has become one staged. The DTA curve/thermogram of propellant RUM show the formation of intermediate product before full-length decomposition. Unlike propellant RUM, DTA curves of propellant 450 and 1220 do not show the formation of intermediate product. Decomposition process of propellant 450 and 1220 accelerate by Al presence. The difference between AP modal on propellant 450 and 1220 show insignificance effect to the amount of decomposition energy consumption. ABSTRAKProses dekomposisi termal propelan padat AP/HTPB jenis RUM, 450 dan 1220 telah dianalisis menggunakan Differential Thermogravimetric 60 (DTG) dengan parameter operasi: suhu 30 - 400⁰C, atmosfer nitrogen berlaju alir 50 ml/menit, dan laju pemanasan 2,5⁰C/menit. Analisis dekomposisi termal adalah langkah awal penelitian kinetika dekomposisi propelan dalam menentukan life time propelan. Kurva TGA menunjukkan bahwa propelan RUM mengalami proses dekomposisi dua tahap sedangkan propelan 450 dan 1220 mengalami proses dekomposisi satu tahap. Kurva DTA/ termogram proses dekomposisi propelan RUM menunjukkan adanya pembentukan produk intermediate sebelum akhirnya terdekomposisi sempurna. Berbeda dengan propelan RUM, termogram propelan 450 dan 1220 tidak menunjukkan terbentuknya produk intermediate. Proses dekomposisi propelan 450 dan 1220 terakselerasi oleh keberadaan Al. Perbedaan modal AP pada propelan 450 dan 1220 ternyata tidak begitu berpengaruh pada nilai konsumsi energi proses dekomposisi.